Our experience of forgotten double-J stents in a tertiary care center - Ahsan Ahmad; Md. Zaid Imbisat; Rakesh K Anand (Asian Journal of Medical Sciences, 2023)
Background: Double-J (DJ) stents have become an essential tool in the field of urology. Forgotten DJ stents are associated with significant morbidity and mortality, if not intervened timely. Aims and Objectives: In this study, we report our experience of forgotten stents related complications, along with its management and steps taken by us in preventing stent-related morbidity. Materials and Methods: We retrospectively analyzed the records of patients presented to the Department of Urology, Indira Gandhi Institute of Medical Sciences, Patna with forgotten or long-term retention of DJ stents from January 2021 to December 2022. All cases were reviewed for age, gender, symptoms, indication of stent insertion, duration of stent insertion, radiological images, and procedures performed for management. Results: The mean age of the patients was 49.23 years. The mean duration of the indwelling stent in situ was 16.61 months. Presenting complaint was flank pain, recurrent urinary tract infection, dysuria, hematuria, and irritative lower urinary tract symptoms. Common indications of indwelling stents were ureteroscopic lithotripsy, percutaneous nephrolithotomy, and Laparoscopic pyeloplasty. Cystoscopy, ureteroscopy, cystolithotripsy, percutaneous nephrolithotomy, and open surgery were done to extract the forgotten DJ stent. Conclusion: Forgotten DJ stents are a source of severe morbidity. Patients and relatives counseling before and after the procedure is necessary in reducing stent-related complications.